Super‐achromatic optical coherence tomography capsule for ultrahigh‐resolution imaging of esophagus. Issue 3 (13th November 2018) - Li, Kaiyan; Liang, Wenxuan; Mavadia‐Shukla, Jessica; Park, Hyeon‐Cheol; Li, Dawei; Yuan, Wu; Wan, Suiren; Li, Xingde
Abstract : Endoscopic optical coherence tomography (OCT) is a noninvasive technology allowing for imaging of tissue microanatomies of luminal organs in real time. Conventional endoscopic OCT operates at 1300 nm wavelength region with a suboptimal axial resolution limited to 8‐20 μm. In this paper, we present the first ultrahigh‐resolution tethered OCT capsule operating at 800 nm and offering about 3‐ to 4‐fold improvement of axial resolution (plus enhanced imaging contrast). The capsule uses diffractive optics to manage chromatic aberration over a full 200 nm spectral bandwidth centering around 830 nm, enabling to achieve super‐achromaticity and an axial resolution of 2.6 μm in air. The performance of the OCT capsule is demonstrated by volumetric imaging of swine esophagus ex vivo and sheep esophagus in vivo, where fine anatomic structures including the sub‐epithelial layers are clearly identified. The ultrahigh resolution and excellent imaging contrast at 800 nm of the tethered capsule suggest the potential of the technology as an enabling tool for surveillance of early esophageal diseases on awake patients without the need for sedation. Abstract : Definitive diagnosis of esophageal diseases is currently under the guidance of endoscopic biopsy at a very limited resolution. The proposed OCT endoscopic capsule is capable of ultrahigh resolution ( 1.8 μm in tissue), depth‐resolved, three‐dimensional and in vivo esophagus imaging, which allows tissue structures situated below the surface to be clearly revealed in real time. Different from traditional endoscopy, this capsule endoscopy is performed on awake patients without sedation.